Downstream Flood Control Programs By Integrated Water Resources and Flood Management Project for Semarang IP-534 - Fajar Setiawan, ST, MT (International Conference on Coastal and Delta Areas, 2015)
Semarang city located in the delta areas. Since 1990 Semarang downtown area increasingly feels the impact of widespread flooding. The flood was caused by two main factors, namely upstream and downstream areas. The high rainfall intensity in the upstream areas is not supported by catchment in the upstream while downstream heavily influenced by sedimentation in the river and people's behavior. Efforts to control the flooding has been done with Integrated Water Resources and FloodManagement Project for Semarang IP-534 through Dam Development with Conservation in the Upper Green Belt, which aim to control flooding and reduce the impact of sediment that will carry over to the downstream area, but these efforts must be balanced with the preservation efforts of flood control infrastructure, as well as the efforts of the community to be aware of the importance of protecting and preserving the environment. Therefore, research is needed to remind and evaluate the management of flood control in the city of Semarang. The data obtained in this study through the literature of various stakeholders, as well as direct observation during a stint in the implementation of development and greenbelt conservation dam Jatibarang. Aspects covered include aspects of institutional, regulatory, community participation as well as the technical and operational aspects. The results showed that the flood control efforts depends on the institutional aspects of the integrity of all stakeholders to work together, and the role of community participation in maintainingand caring for the environment. Therefore we need a system of management and flood management together that included all the stakeholders from the central government, provincial and municipal governments to jointly support the flood control efforts, and the role of the community in supporting the efforts of the management and flood control Semarang not only downstream communities but also communities in the upper reaches by still maintaining the protected area because it serves as a deterrent catchment areas and sedimentation through conservation efforts.